Nature images are more visually engaging than urban images: evidence from neural oscillations in the brain - McDonnell, Amy S.; LoTemplio, Sara B.; Scott, Emily E.; Strayer, David L. (Frontiers in Human Neuroscience, 2025)
IntroductionAttention Restoration Theory posits that urban environments place high demand on our attentional systems, which can fatigue over time and lead to impairments in performance. On the contrary, natural environments are proposed to visually engage our attention but in a less demanding way, allowing for the recuperation of attentional resources and subsequent improvements in attentional performance. However, the neural mechanisms underlying these varying attentional demands remain poorly understood. The current study utilized electroencephalography (EEG) to explore attention-related brain activity when individuals view images of nature and urban environments.MethodsIn a between-subjects design, 58 participants viewed 10-min of either nature or urban images while brain activity was recorded. Frequency-domain measures of parietal alpha and frontal theta were extracted from the raw EEG data to quantify visual engagement and cognitive demand, respectively.ResultsParticipants that viewed nature images displayed significantly lower parietal alpha power than participants that viewed urban images, suggesting nature scenes are more visually engaging than urban scenes. Participants that viewed nature images also displayed trends toward lower frontal theta power than participants that viewed urban images, suggesting that nature scenes are less cognitively demanding to process, though this effect was not statistically significant. Lastly, nature images were self-reported to be more restorative than urban images.DiscussionTaken together, these results suggest that natural scenes are visually engaging, but not in a cognitively demanding fashion. This aligns with Attention Restoration Theory and prior literature suggesting that nature scenes engage effortless, involuntary attention while allowing effortful attention to rest and recover.